2018
DOI: 10.1038/s41393-018-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of disrupted clock gene expression in males with tetraplegia: a crossover randomized placebo-controlled trial of melatonin supplementation

Abstract: Financial support was provided from the Throne Holst Foundation, Sunnaas Rehabilitation hospital and the University of Ferrara (FAR2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Following an SCI, the mRNA expression of clock genes (i.e., period circadian regulator (PER)-1 and -2, and REV-ERBα) are disrupted. This may impact diurnal variations in immune cell counts given that PER-1 and -2 clock genes are strongly linked with the oscillations seen in leukocyte concentrations in able-bodied adults [24]. Therefore, it could be interpreted that the HFHC experimental meal provided in this study prevented a natural diurnal rise in leukocytes.…”
Section: Diurnal Variation Impacts Circulating Immune Cell Countmentioning
confidence: 90%
“…Following an SCI, the mRNA expression of clock genes (i.e., period circadian regulator (PER)-1 and -2, and REV-ERBα) are disrupted. This may impact diurnal variations in immune cell counts given that PER-1 and -2 clock genes are strongly linked with the oscillations seen in leukocyte concentrations in able-bodied adults [24]. Therefore, it could be interpreted that the HFHC experimental meal provided in this study prevented a natural diurnal rise in leukocytes.…”
Section: Diurnal Variation Impacts Circulating Immune Cell Countmentioning
confidence: 90%
“…Disrupted circadian rhythm is a common symptom following TBI, and is reflected by the fact that up to 50% of these patients suffer from sleep disorders that are additionally characterised by aberrant expression patterns of clock genes in mononuclear blood cells [ 220 , 221 , 222 ]. Similar to TBI patients, those with cervical spinal cord injury commonly develop sleep disorders that are accompanied by circadian disruptions like dysregulated circadian rhythm and course of melatonin production [ 223 , 224 ], core body temperature [ 225 ], and aberrant expression patterns of clock genes in peripheral blood mononuclear cells [ 226 ]. Sleep abnormalities have been shown to negatively affect the outcome of TBI [ 227 ], and a recent study in mice shows involvement of circadian regulation in the neuroinflammation and blood–spinal cord barrier disruption following TSCI [ 228 ]; therefore, different kinds of chronotherapeutics have already been clinically tested.…”
Section: Interaction Of Tsci and Tbimentioning
confidence: 99%
“…The reduction of evening melatonin, often referred to as the ‘sleep hormone’, could lead to insomnia and was observed in patients suffering from spinal cord injury and TBI [ 224 , 231 , 232 , 233 ]. As melatonin acts as a neuroprotector and reduces oxidative stress as well as neuroinflammation, it might be a promising drug to treat sleep disorders following TSCI and TBI [ 226 , 234 , 235 ].…”
Section: Interaction Of Tsci and Tbimentioning
confidence: 99%
“…In 2000, Zeitzer and colleagues showed that complete cervical SCI, which cuts the suprachiasmatic nuclei to superior cervical ganglion pathway, is associated with near abolition of circadian melatonin rhythmicity and a markedly reduced circulating level 69. These findings have been replicated by others 7074. Other endocrine rhythms similarly modified by circadian influences, such as cortisol and thyroid-stimulating hormone, do not appear markedly affected by cervical SCI, however, the temperature is affected 75.…”
Section: Effect Of Sci On Circadian Rhythm Sleep-wake Disorders (Crswd)mentioning
confidence: 99%
“…While the studies suggested some subjective improvements in sleep, both trials were underpowered statistically to demonstrate any effect on objective sleep variables. More recently, Kostovski and colleagues have shown that exogenous melatonin administration in tetraplegia can normalize clock gene expression in peripheral blood 74. The symptomatic and longer-term physiological effects of these changes are as yet unknown.…”
Section: Management Of Sleep Disorders In Individuals With Scimentioning
confidence: 99%